The Effect of Loan Interest Expense on Net Profit at PT Summarecon Agung Tbk - Alexandra, Geraldine Eileen; Kurnia, Josefina Aurelia; Manurung, Elizabeth Tiur (Universitas Mohammad Husni Thamrin, 2025)
This study aims to analyze the effect of loan interest expense on net profit of PT Summarecon Agung Tbk in the period 2017 to 2024. In the capital-intensive property industry, the use of debt as a source of funding is common. However, increasing debt will result in interest expenses that can affect the company's financial performance, especially net profit. The data used in this study are loan expenses (financial costs) and net profit obtained from the company's financial statements. The simple linear regression method is used to test the relationship between the two variables. The results of the regression analysis show that there is an insignificant positive relationship between loan interest expense and net profit, with a coefficient of 0.4039 and a p-value of 0.3157. This indicates that every 1 unit increase in loan interest expense will increase net profit by 0.4039 units. In addition, the intercept value also has a high p-value (0.1931) indicating that other factors may also affect net profit. These findings indicate that interest expense is not the only factor that determines a company's net profit, and that external factors such as property market dynamics, monetary policy, and the company's internal operational strategy play a significant role. The low adjusted R-square value indicates that the independent variables in this study only explain a small part of the variation in net profit. The conclusion of this study is that loan interest expense can contribute to increasing net profit, but other external factors also need to be considered in the company's financial analysis.